MODIFIED PROBABILISTIC NEURO-FUZZY NETWORK FOR TEXT DOCUMENTS PROCESSING - Bodyanskiy, Yevgeniy; Pliss, Irina; Volkova, Valentyna (International Journal of Computing, 2014)
We consider the problem of text processing (classification problem) using the modification of the probabilistic neural network proposed by D. Specht. Since classes often overlap during texts processing, there were introduced the modification that implements a procedure of fuzzy inference. For this into the network were introduced two additional layers. The results of the outputs of the network are levels of belonging each text document to each of the possible classes.